Teachers’ Views on the Reputation of the Teaching Profession - GÜLBAHAR, Bahadır; NAMOĞLU, Esma (PEARSON JOURNAL, 2024)
This study aims to obtain teachers’ views on the reputation of the teaching profession, to determine the factors that affect the reputation of the profession positively and negatively through these views. The research was conducted as a phenomenological study from qualitative research methods. The study group of the research consists of 35 teachers selected among the teachers working in the central districts of Ankara in the 2023-2024 academic year. The personal information of these teachers was collected through a demographic information form, and then their views on the reputation of the teaching profession were obtained through a semi-structured interview consisting of 5 questions. As a result of the research, opinions that teaching is a reputable profession, opinions that teaching is not a reputable profession, factors that positively affect the reputation of teaching profession, factors related to personal characteristics that positively affect the reputation of teaching profession, social and environmental factors that positively affect the reputation of teaching profession, factors related to personality that negatively affect the reputation of teaching profession, environmental factors that negatively affect the reputation of teaching profession and suggestions for improving the reputation of teaching profession were determined.